SYSTOLIC ARTERIAL HYPERTENSION: THE PLACE OF ANGIOTENSIN II RECEPTOR BLOCKERS - D. V. Nebieridze (Российский кардиологический журнал)
Systolic arterial hypertension: the place of angiotensin II receptor blockers.